Los dúo 2 [compact disc] - Gabriel, Juan (Fonovisa, 2015)
Juan Gabriel releases the follow up to his successful Los Duo release. More of his classic hits are transformed into duets featuring Marc Anthony, Paulina Rubio, Wisin, and more.